Respuesta :
Answer:
See below
Step-by-step explanation:
[tex]\textbf{Part A: } \text{ If }h(x) = f (x) + g(x) \text{, solve for } h(x) \text{ in simplest form.}[/tex]
We have
[tex] f (x) = \log_3(x) + 3 [/tex]
and
[tex]g(x) = \log_3(x^3) - 1[/tex]
Thus
[tex]h(x) = f (x) + g(x) = (\log_3(x) + 3) + ( \log_3(x^3) - 1) = \log_3(x) + 3 + \log_3(x^3) - 1[/tex]
[tex]= \log_3(x) + \log_3(x^3) + 2[/tex]
Recall the property of logarithms:
[tex]\boxed{\log_b(n\cdot m) = \log_b(n) + \log_b(m)}[/tex]
then,
[tex]\log_3(x) + \log_3(x^3) + 2 = \log_3(x\cdot x^3) +2 = \boxed{\log _3(x^4)+2}[/tex]
================================================================
[tex]\textbf{Part B: } \text{Determine the solution to the system of nonlinear equations of } f(x) \text{ and } g(x).[/tex]
I am assuming that the system of equations is
[tex]$\left \{ {{ f (x) = \log_3(x) + 3 } \atop {g(x) = \log_3(x^3) - 1}} \right$[/tex]
and you probably want the solution when [tex]f(x)=g(x)[/tex] I will name it [tex]y[/tex], thus
[tex]$\left \{ {{ f (x) = \log_3(x) + 3 } \atop {g(x) = \log_3(x^3) - 1}} \right \implies \left \{ {{y= \log_3(x) + 3 } \atop {y = \log_3(x^3) - 1}} \right$ [/tex]
We should just solve
[tex]\log_3(x) + 3 = \log_3(x^3) - 1 [/tex]
[tex]\log_3(x) - \log_3(x^3) = - 4[/tex]
[tex]\log_3 \left(\dfrac{x}{x^3} \right) = - 4[/tex]
[tex]\log_3 \left(\dfrac{1}{x^2} \right) = - 4[/tex]
[tex]\log_3 (x^{-2}) = - 4[/tex]
[tex]-2\log_3 (x) = - 4[/tex]
[tex]\log_3 (x) = 2 \iff 3^2 = x \implies \boxed{x= 9} [/tex]